From Responsibility to Reward: Investigating the Mediating Effect of Accounting Conservatism on CSR and Dividend Policy in Pakistan (Journal of Asian Development Studies, 2025)
The investigation within this study examines the complex relationship between Corporate Social Responsibility (CSR), Accounting Conservatism (AC), and Dividend Policy (DP) in the context of ethical financial decision-making that is spreading throughout the world. The analysis looks at data gathered from 200 Pakistani listed firms spanning 2014-2024 to understand how AC serves as a linking mechanism for CSR programs to sustain dividends. The analysis, conducted through a dynamic two-step system Generalized Method of Moments (GMM) model, demonstrates that CSR significantly impacts accounting conservatism, thereby enhancing dividend policy. The empirical results show that CSR has a powerful positive impact on accounting conservatism (β = 0.0316, p = < 0.01), and subsequently on dividend policy (β = 0.1273, p = < 0.1). Moreover, the mediation analysis shows that the relationship between CSR and dividend policy is partially mediated by accounting conservatism, indicating that conservatism plays a mediating role between ethical behavior and the reward of shareholders. The research offers a new perspective on the emerging market situation, delivering pragmatic value to both business decision-makers and regulatory bodies who seek financial prudence combined with stakeholder responsibility. Future studies should pursue in-depth investigations into behavioral and governance-related mediators using the findings presented in this study.